Speech and silence in the system of human communication - BENDJELLOUL, Abdelkader (Journal of Human Sciences, 2005)
This paper aims to show the increasing importance in contemporary studies of language of the use of silence as an element of human communication both from a qualitative and a quantitative point of view. It is more and more considered as an integral part of the cultural system of a speech community, of the structure of their conversations, and of the conversational behaviour and strategy of an interactant.